IDOSOS E DIREITO À EDUCAÇÃO - Paulo Roberto Barbosa Ramos (Revista de Políticas Públicas, 2005)
This article tries to approaeh the elde,y and his right to Education. It points out the written Constitution as an invention of the Modernity, important to stablish the fundamental ribts conquist of social fights, in the perspective ofbuilding an inclusive and democraüc society. Education is stressed as eldery’s right and as a space of the young formation in order to clirninate prejudice.